Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0883073818789320
|View full text |Cite
|
Sign up to set email alerts
|

Objective Eye Tracking Deficits Following Concussion for Youth Seen in a Sports Medicine Setting

Abstract: Quantification of visual deficits may help to identify dysfunction following concussion. We evaluated eye-tracking measurements among adolescents within 10 days of concussion and healthy control participants. Patients who reported to 2 tertiary care sport concussion clinics within 10 days of concussion completed an objective eye tracking assessment. Seventy-nine participants completed the study, 44 with concussion (mean age = 14.1 ± 2.2 years, 39% female) and 35 controls (mean age = 14.3 ± 2.4 years, 57% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 32 publications
(62 reference statements)
0
37
0
Order By: Relevance
“…One study also reported a comparison of their smooth pursuit synchronization index outcome with a traditional measure of velocity error to validate their outcome measure (Contreras et al, 2011). One study used commercial software (Oculogica, Inc.) to process their data (Howell et al, 2018) and referred to several previous studies that had also used this software to suggest its validity. However, validity of the commercial software is unclear, as it should be noted that none of the studies that were referenced examined or reported the data processing involved.…”
Section: Reliability and Validitymentioning
confidence: 99%
See 4 more Smart Citations
“…One study also reported a comparison of their smooth pursuit synchronization index outcome with a traditional measure of velocity error to validate their outcome measure (Contreras et al, 2011). One study used commercial software (Oculogica, Inc.) to process their data (Howell et al, 2018) and referred to several previous studies that had also used this software to suggest its validity. However, validity of the commercial software is unclear, as it should be noted that none of the studies that were referenced examined or reported the data processing involved.…”
Section: Reliability and Validitymentioning
confidence: 99%
“…Several studies (Maruta et al, 2010b;Contreras et al, 2011;Cifu et al, 2015;Diwakar et al, 2015;DiCesare et al, 2017;Wetzel et al, 2018;Stuart et al, 2019b) did provide some details regarding definitions but these substantially varied between the studies ( Table 2, Supplementary Table 1). Three studies provided no outcomes specific to traditional eye movements (Suh et al, 2006;Murray et al, 2014;Howell et al, 2018), but instead reported on novel outcomes of "Gaze Stabilization" (a fixation measure), "Eye Skew" (an asymmetry measure), and "Oculomotor error" (a smooth pursuit measure) that authors developed for their individual studies. Overall, reporting of possible eye movement outcomes from the eye-tracking devices substantially varied between studies.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations